Structural response spectra for different soil condition under earthquake loading - Entika, Christie Lanjing (2011)
The extent or degree of damage due to earthquake depends very much on the response of ground and structure to earthquake loading. One of the main concerns with respect to ground response to earthquake loading is seismic wave amplification. Seismic wave amplification causes large accelerations to be transferred to structure especially when the resulting seismic wave frequencies match with the structures resonant frequencies. Such phenomenon may lead to catastrophic damages and lost. In this study, the aim is to produce structural response spectra for different soil condition under earthquake loading with the objectives to determine peak ground accelerations at the ground surface for three locations in Malaysia, to determine peak accelerations at the highest point of low rise, medium rise and high rise building and as well as to investigate amplifications of ground and structure accelerations. The ground condition of each location of interest is presented by one bore log data which are collected at site and in each location the response of three types of building are investigated. The soil and the building are model as soil structure model using finite element method. In each location, the response of ground and structure are being investigated by applying synthetic time histories according to the three selected locations respectively. At the end of this study, response spectra are produced for ground accelerations at bedrock, ground accelerations at ground surface and peak accelerations of the highest point of every type of building. From the response spectra, peak ground acceleration at ground surface and peak accelerations of the highest point of every type of building are determined and amplification has been investigated.